Stress mediators and immune dysfunction in patients with acute cerebrovascular diseases - Liesz, Arthur; Rüger, Holger; Purrucker, Jan; Zorn, Markus; Dalpke, Alexander; Möhlenbruch, Markus Alfred; Englert, Stefan; Nawroth, Peter Paul; Veltkamp, Roland (PLOS ONE, 2013)
Background Post-stroke immune depression contributes to the development of infections which are major complications after stroke. Previous experimental and clinical studies suggested that humoral stress mediators induce immune dysfunction. However, prospective clinical studies testing this concept are missing and no data exists for other cerebrovascular diseases including intracerebral hemorrhage (ICH) and TIA. Methods We performed a prospective clinical study investigating 166 patients with TIA, ischemic and hemorrhagic stroke. We measured a broad panel of stress mediators, leukocyte subpopulations, cytokines and infection markers from hospital admission to day 7 and on follow-up after 2-3 months. Multivariate regression analyses detected independent predictors of immune dysfunction and bacterial infections. ROC curves were used to test the diagnostic value of these parameters. Results Only severe ischemic strokes and ICH increased some catecholamine metabolites, ACTH and cortisol levels. Immunodysfunction was eminent already on hospital admission after large brain lesions with lymphocytopenia as a key feature. None of the stress mediators was an independent predictor of lymphocytopenia or infections. However, lymphocytopenia on hospital admission was detected as an independent explanatory variable of later infections. NIHSSS and lymphocytopenia on admission were excellent predictors of infection. Conclusions Our results question the present pathophysiological concept of stress-hormone mediated immunodysfunction after stroke. Early lymphocytopenia was identified as an early independent predictor of post-stroke infections. Absence of lymphocytopenia may serve as a negative predictive marker for stratification for early antibiotic treatment.